2014
DOI: 10.1557/opl.2014.762
|View full text |Cite
|
Sign up to set email alerts
|

New Alumosilicate Fillers Based on Sedimentary Rocks for Asphalt Concrete

Abstract: Asphalt concrete is the most common material for highway and motorway construction. The quality of asphalt is determined, to a large extent, by properties of asphalt binder. Fillers, which are mineral powders from carbonate rocks and aggregates fines, such as limestone and dolomite, are often used in the composition of bitumen mastics affecting the performance of asphalt.This article explores the feasibility of using the fines of aluminosilicate sedimentary rocks as fillers. These materials are composed of cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Cui et al [14] found that the interfacial adhesion in wet conditions could be improved by mixing a silane, amine or rubbery polymer into the bitumen. Strokova et al [15] explored the feasibility of using the fines of aluminosilicate sedimentary rocks as fillers, and the results showed that such treatment provided sufficient structural stability of obtained materials and resulted in the reduction of water absorption of asphalt, improved water resistance (up to 2.5 times) and also, in reduced swelling (up to 9 times). The second method was to modify the asphalt binder.…”
Section: Introductionmentioning
confidence: 99%
“…Cui et al [14] found that the interfacial adhesion in wet conditions could be improved by mixing a silane, amine or rubbery polymer into the bitumen. Strokova et al [15] explored the feasibility of using the fines of aluminosilicate sedimentary rocks as fillers, and the results showed that such treatment provided sufficient structural stability of obtained materials and resulted in the reduction of water absorption of asphalt, improved water resistance (up to 2.5 times) and also, in reduced swelling (up to 9 times). The second method was to modify the asphalt binder.…”
Section: Introductionmentioning
confidence: 99%